2007
DOI: 10.1111/j.1468-2389.2007.00376.x
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Judgments of Ethnically Diverse Applicants During Personnel Selection: A study at the Dutch police

Abstract: A judgment-analysis study was used to investigate assessors' judgment processes, evaluating ethnic minority vs ethnic majority applicants. Sixteen ethnic majority assessors judged 5089 applicants during the Dutch police officer selection procedure, with each assessor judging 30 ethnic minority applicants minimally. Information from an employment interview, an assessment center, and a Big Five personality test were combined into a final selection advice. Results showed that as much as or more information source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…These scores are integrated into an employment recommendation. The dimensions in the final recommendation are: Communication Skills, Social Skills, Empathy, Initiative, Flexibility, Stress Tolerance, Authority, Decisiveness, Tolerance Towards Others, Integrity, and Self-Understanding (for definitions, see De Meijer, Van Zielst, and Van der Molen, 2007). A seven-point Likert scale ranging from 1 (extremely weak) to 7 (excellent) is used to evaluate the behavior on the 11 dimensions.…”
Section: Final Employment Recommendationmentioning
confidence: 99%
“…These scores are integrated into an employment recommendation. The dimensions in the final recommendation are: Communication Skills, Social Skills, Empathy, Initiative, Flexibility, Stress Tolerance, Authority, Decisiveness, Tolerance Towards Others, Integrity, and Self-Understanding (for definitions, see De Meijer, Van Zielst, and Van der Molen, 2007). A seven-point Likert scale ranging from 1 (extremely weak) to 7 (excellent) is used to evaluate the behavior on the 11 dimensions.…”
Section: Final Employment Recommendationmentioning
confidence: 99%
“…Several recent studies have shown evidence of unfavorable employment decisions based on subtle forms of discrimination (Regmi, Naidoo, & Regmi, 2009) and negative stereotypic attitudes held against immigrant job applicants (Agerström & Rooth, 2008;Cotton, O'Neill, & Griffin, 2007). de Meier, Born, Zielst, and van der Molen (2007) argue that interviewers' unfamiliarity with foreign-born applicants' culture and traditions, as well as lack of experience with interviewing foreign-born applicants, increase the risk of stereotypic activation and biased employment decisions. They found that even highly experienced recruiters were less secure of their own judgments, used more sources of information, and relied on a larger number of irrelevant cues when evaluating ethnic minority applicants compared to ethnic majority applicants.…”
mentioning
confidence: 99%
“…Predominantly discussed in interviewing studies, some show more experienced recruiters to be less biased towards stigmatised applicants, whereas others show more bias. De Meijer, Born, van Zielst, and van der Molen (), for instance, found that experienced recruiters used more irrelevant information when judging ethnic minorities, perhaps because they feel overconfident and hence, engage in Type 1 processing.…”
Section: Contingencies Of Biased Resume Screeningmentioning
confidence: 99%
“…There is, nevertheless, an ongoing debate about the validity of implicit attitude measures and whether any relation with behaviour can be expected and established outside the lab(Oswald, Mitchell, Blanton, Jaccard, & Tetlock, 2015).Finally, there is also a debate about the role of decision-makers' expertise. Predominantly discussed in interviewing studies, some show more experienced recruiters to be less biased towards stigmatised applicants, whereas others show more bias De Meijer, Born, van Zielst, and van der Molen (2007),. for instance, found that experienced recruiters used more irrelevant information when judging ethnic minorities, perhaps because they feel overconfident and hence, engage in Type 1 processing.…”
mentioning
confidence: 99%